Teaching Materials for Indonesian Literature Lectures Based on Respect Education: A Development Research - Atika Wasilah; Safinatul Hasanah Hrp; Achmad Yuhdi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to create innovative humanistic teaching materials based on respect education in teaching literature in schools to address the persistent issue of bullying. Methodology: This research follows a Research and Development (R&D) approach, utilizing the 4-D development model introduced by Sivasailam Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel. This model consists of four key stages: Define, Design, Develop, and Disseminate. Main Findings: Analysis of the need for Teaching Materials for Indonesian Literature Teaching Lectures Based on Respect Education begins with an observation of the learning conditions in the literature teaching course at the Indonesian Language and Literature Education Study Program. This observation was carried out by interviewing the lecturers in charge of the literature teaching course. The results of the observation stated that the learning conditions of students in the literature teaching course were still not optimal in the implementation process, and the availability of teaching materials provided by the lecturers. The results of the observation also stated that teaching materials for literature teaching based on respect education had never been implemented or developed. Novelty/Originality of this study: The results of the study showed that from the four aspects in the analysis of teaching material needs which include content, language, presentation, and graphics, it was concluded that students and lecturers 'strongly agree' to develop teaching materials for literature teaching based on respect education.